Applying Self-Determination Theory (SDT) In Game-Based Learning (GBL) To Teach Grammar For TOEFL For University Students - Ria Kusrini, Nurul Azizah; Agustyarini, Yashinta (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study aimed to find out the intrinsic motivation from Self-Determination Theory (SDT) of university students in learning grammar for TOEFL through a gamified way. The game platform used was Kahoot. this study employed qualitative descriptive research as it focused on the responds of the students in doing TOEFL-like test in Kahoot.it, and then analyzing the students’ feedback toward the game, the materials, and the activities. The result showed that the game was employed in an experimental setting to examine the influence of Autonomy, Relatedness, and Competence (ARC) support on player engagement and motivation. The intrinsic motivation components were evaluated and they indicate certain conclusions. In the online game context intrinsic motivation is enhanced by the perspective of winning and/or getting a reward. Implementing language games into the learning process will bring variety, break monotony, enliven classes, and motivate students to work. Rewards, points, levels are forms of extrinsic motivators, but the whole gaming experience touches significantly the intrinsic motivation aspects.